Ceramic-based composite material with water and oxygen corrosion resistance and high heat insulation performance and preparation method of ceramic-based composite material

Through the gradient concentration precursor impregnation liquid and melting and seepage reaction technology, a mixed dense layer is formed, which solves the problem of insufficient corrosion and thermal insulation performance of ceramic matrix composites in high-temperature water and oxygen environments, and realizes the efficient anti-water oxygen corrosion and isolation of the material Thermal effect extends its service life.

CN119306514AActive Publication Date: 2025-01-14AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411594224.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-14
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

Traditional ceramic matrix composites are susceptible to water-oxygen corrosion in high-temperature water-oxygen environments, and the existing thermal insulation coatings crack and peel due to mismatched thermal expansion coefficients, which cannot effectively improve their service life.

Method used

The precursor impregnation liquid with gradient concentration is used to prepare porous ceramic-based composite materials through PIP process, and the melting and permeation reaction is carried out in the silica powder to form rich in ytterbium silicate, titanium silicate, hafnium silicate, zirconium silicate, A hybrid dense layer of magnesium silicate and fiber framework improves its resistance to water and oxygen corrosion and thermal insulation.

Benefits of technology

It realizes excellent anti-water oxygen corrosion and high thermal insulation properties of ceramic matrix composites in high-temperature water oxygen environments, avoids coating failure and peeling, extends the service life of the material, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306514A_ABST
    Figure CN119306514A_ABST
Patent Text Reader

Abstract

The invention relates to a ceramic-based composite material with water and oxygen corrosion resistance and high heat insulation performance and a preparation method thereof. The method comprises the following steps: primarily densifying a porous ceramic-based composite material by using a PCS solution as an impregnation liquid through a PIP process; the preparation method comprises the following steps: preparing n gradient concentration steeping liquor which contains a solid component A, a solid component B and a PCS solution, densifying the preliminarily densified ceramic matrix composite material by using the n gradient concentration steeping liquor through a PIP process to obtain the ceramic matrix composite material of which the surface layer contains the solid component A and the solid component B, the content of the solid component A in the surface layer is in a decreasing trend, and the content of the solid component B in the surface layer is in a decreasing trend. The content of the solid component B is gradually increased in the surface layer; and then putting the mixture into silicon dioxide to carry out infiltration reaction to prepare the ceramic-based composite material. The prepared ceramic-based composite material has water-oxygen corrosion resistance and high heat insulation performance, the water-oxygen corrosion resistance and high heat insulation component bonding strength is higher, the protection effect is better, and the service life is longer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic-based composite material preparation, and in particular relates to a ceramic-based composite material having both water-oxygen corrosion resistance and high heat insulation performance and a preparation method thereof. Background Art

[0002] Ceramic-based composites are widely used in the aerospace field due to their excellent high temperature resistance, low density, high specific strength and high toughness. However, as the working conditions become more and more harsh, traditional ceramic-based composites are susceptible to water-oxygen corrosion in high-temperature environments containing water vapor and oxygen, resulting in degradation of material performance and thus affecting their service life. In addition, during service, the extremely high temperature heat flow on the surface will quickly heat the ceramic-based composites, causing the temperature of the internal materials to rise sharply, reducing the service performance and service life of the materials. Therefore, in order to improve the service performance of ceramic-based composites, it is urgent to develop a ceramic-based composite material that has both resistance to high-temperature water-oxygen corrosion and high thermal insulation performance.

[0003] In order to improve the water vapor corrosion resistance and thermal insulation performance of ceramic-based composite materials, thermal spraying, plasma deposition and slurry coating are generally used to prepare environmental barrier coatings and thermal barrier / environmental barrier coatings on their surfaces to improve the water oxygen corrosion resistance of ceramic-based composite materials. However, due to the mismatch in thermal expansion coefficients between the coating material and the ceramic-based composite matrix, multiple layers of coatings need to be applied to enhance the physical compatibility between the coatings. Although this method can alleviate the thermal mismatch stress between coatings to a certain extent, it cannot fundamentally change the problem of thermal expansion coefficient mismatch between coatings / coatings and coatings / matrix. Therefore, at relatively low bonding strength, environmental barriers and thermal barriers / environmental barrier coatings will still crack and peel off during service, further reducing their water oxygen corrosion resistance. In addition, due to the large number of types and layers of environmental barrier coatings and thermal barrier / environmental barrier coatings, they are generally unable to be formed in one go, which limits the further application of this method.

[0004] Chinese patent CN202110573926.X discloses a method for preparing a bonding layer / Yb on the surface of a ceramic matrix composite material by thermal spraying 2 Si 2 O 7 / Yb 2 SiO 5 / Modified Gd 2 Zr 2 O 7Thermal / environmental barrier composite coating system, and a method for improving the water-oxygen corrosion resistance and thermal insulation capabilities of ceramic-based composite materials. In this patent, the difference between the thermal expansion coefficients of each layer is the main cause of interlayer cracking, causing the coating interface to become a weak area in the coating system that is prone to failure. The composite coating has a large number of coating layers. Although it can alleviate the mismatch of thermal expansion coefficients between different materials to a certain extent, it introduces more coating interfaces, and more weak areas will fail and peel off due to thermal mismatch stress, thereby weakening the protective effect of the coating and reducing the protective life of the coating.

[0005] Chinese patent CN202410315852.3 discloses a ceramic-based composite material modified by a multiphase oxide ceramic and a preparation method thereof. The method first introduces a high-entropy rare earth disilicate into a porous ceramic-based composite material by a slurry impregnation method, and then further densifies the composite material by embedding and infiltrating with glass powder. However, this method still has certain limitations. The porosity of the SiC / SiC composite material after CVI densification is relatively small, and it is difficult to introduce a high-entropy rare earth disilicate slurry into the densified composite material by vacuum impregnation. In addition, although high-entropy rare earth disilicates also have anti-water vapor corrosion effects, they have little effect on the thermal insulation effect of ceramic-based composite materials, and cannot have both anti-water oxygen corrosion and improved thermal insulation performance.

[0006] Therefore, how to ensure the mechanical properties of ceramic-based composite materials while making them have both resistance to high-temperature water-oxygen corrosion and high thermal insulation performance is a key issue in improving their service life in high-temperature water-oxygen environments. Summary of the invention

[0007] In order to solve one or more technical problems existing in the prior art, the present invention provides a ceramic-based composite material having both water-oxygen corrosion resistance and high thermal insulation performance and a preparation method thereof. The ceramic-based composite material prepared by the method of the present invention has excellent water-oxygen corrosion resistance (high-temperature water-oxygen corrosion resistance), good thermal insulation effect, low preparation cost, and can realize the integrated preparation of a ceramic-based composite material having both water-oxygen corrosion resistance and high thermal insulation performance.

[0008] In a first aspect, the present invention provides a method for preparing a ceramic-based composite material having both water-oxygen corrosion resistance and high thermal insulation performance, the method comprising the following steps:

[0009] (1) Preparation of porous ceramic-based composite materials;

[0010] (2) using a polycarbosilane solution as an impregnation solution, and densifying the porous ceramic-based composite material through a precursor impregnation and cracking process to obtain a preliminarily densified ceramic-based composite material;

[0011] (3) preparing n precursor impregnation solutions with gradient concentrations, each precursor impregnation solution comprising a solid component A, a solid component B and a polycarbosilane solution, wherein the solid component A comprises ytterbium oxide powder, titanium oxide powder and hafnium oxide powder, and the solid component B comprises zirconium oxide powder and magnesium oxide powder;

[0012] (4) densifying the preliminarily densified ceramic matrix composite material by a precursor impregnation pyrolysis process (PIP process) in sequence using n precursor impregnation solutions of gradient concentrations to obtain a ceramic matrix composite material having a surface layer containing a solid component A and a solid component B; wherein the content of the solid component A in the surface layer shows a decreasing trend, and the content of the solid component B in the surface layer shows an increasing trend;

[0013] (5) The ceramic-based composite material having a surface layer containing solid component A and solid component B is placed in a silicon dioxide powder for infiltration reaction to obtain a ceramic-based composite material having both water and oxygen corrosion resistance and high thermal insulation performance.

[0014] Preferably, in the precursor impregnation solutions of n gradient concentrations, the content of solid component A contained therein shows a decreasing trend, and the content of solid component B contained therein shows an increasing trend; n≥2 and n is a positive integer; the concentration range of the solid component A in the precursor impregnation solutions of n gradient concentrations is 10-50wt%, and the concentration range of the solid component B in the precursor impregnation solutions of n gradient concentrations is 10-50wt%; and / or the surface layer of the ceramic-based composite material having both resistance to water and oxygen corrosion and high thermal insulation properties is a mixed dense layer comprising ytterbium silicate, titanium silicate, hafnium silicate, zirconium silicate, magnesium silicate, silicon carbide, silicon dioxide and a fiber skeleton, wherein the total content of ytterbium silicate, titanium silicate and hafnium silicate shows a decreasing trend in the surface layer, and the total content of zirconium silicate and magnesium silicate shows an increasing trend in the surface layer.

[0015] Preferably, in step (1), the porous ceramic-based composite material is obtained by depositing an interface layer on the fibers of a fiber braid; preferably, the fiber braid is a carbon fiber braid or a silicon carbide fiber braid; preferably, the density of the fiber braid is 0.4 to 0.7 g / cm 3 Preferably, the interface layer is one or more of a pyrolytic carbon interface layer, a silicon carbide interface layer or a boron nitride interface layer; Preferably, the density of the porous ceramic matrix composite material is 0.8 to 1.2 g / cm 3 .

[0016] Preferably, in step (2), the polycarbosilane solution is a xylene solution of polycarbosilane, preferably, the mass fraction of polycarbosilane in the polycarbosilane solution is 35-60%; and / or the precursor impregnation and cracking process is repeated multiple times until a density of 1.3-1.5 g / cm is obtained. 3 Preliminary densification of ceramic matrix composites.

[0017] Preferably, in step (3): the polycarbosilane solution contained in the precursor impregnation solution is a xylene solution of polycarbosilane, preferably, the mass fraction of polycarbosilane in the polycarbosilane solution is 10-30%; the particle size D50 of the ytterbium oxide powder, titanium oxide powder and / or hafnium oxide powder is 0.1 μm to 1 μm; and / or the solid component A contains 40-60% of ytterbium oxide powder, 20-30% of titanium oxide powder and 20-30% of hafnium oxide powder by mass fraction.

[0018] Preferably, in step (3): the particle size D50 of the zirconium oxide powder and / or the magnesium oxide powder is 0.1 μm to 1 μm; and the solid component B contains 40 to 60% of zirconium oxide powder and 40 to 60% of magnesium oxide powder by mass.

[0019] Preferably, in step (4): the thickness of the ceramic-based composite material containing solid component A and solid component B on the surface layer is 500-2000 μm; and / or the density of the ceramic-based composite material containing solid component A and solid component B on the surface layer is 1.8-2.1 g / cm 3 .

[0020] Preferably, in step (5): the particle size D50 of the silica powder is 0.1 μm to 1 μm; the temperature of the infiltration reaction is 1400 to 1700°C, the time of the infiltration reaction is 60 to 180 min; and / or the heating rate to the infiltration reaction temperature is 2 to 4°C / min.

[0021] Preferably, in step (5): the thickness of the mixed dense layer is 500-2000 μm; the density of the ceramic-based composite material having both water-oxygen corrosion resistance and high thermal insulation performance is 2.2-2.5 g / cm 3 The ceramic-based composite material having both water-oxygen corrosion resistance and high thermal insulation performance has a thermal conductivity of no more than 5 W / m·K at 1500°C and has excellent water-oxygen corrosion resistance at 1200-1500°C.

[0022] In a second aspect, the present invention provides a ceramic-based composite material having both water-oxygen corrosion resistance and high thermal insulation performance, which is prepared by the preparation method described in the first aspect of the present invention.

[0023] Compared with the prior art, the present invention has at least the following beneficial effects:

[0024] (1) The present invention prepares Yb in a certain thickness area on the surface of the composite material 2 SiO 5 、TiSiO 4 、HfSiO 4、ZrSiO 4 Mg 2 SiO 4 , SiC and SiO 2 matrix, and a mixed dense layer of fiber skeleton; the present invention finds that Yb 2 SiO 5 、TiSiO 4 With good high temperature phase stability and excellent high temperature water corrosion resistance, HfSiO 4 It has extremely high resistance to high temperature oxidation and excellent resistance to oxidation corrosion, and can provide composite materials with better resistance to high temperature water vapor corrosion; ZrSiO 4 and Mg 2 SiO 4 It has good phase stability and thermophysical properties, has the advantages of low sintering rate and low thermal conductivity, and can provide excellent thermal insulation for composite materials; molten SiO 2 It can further fill the pores on the surface of the composite material, prevent oxygen from diffusing along the pores to the core, and prevent the core from oxidizing; the fiber skeleton can effectively ensure that the mixed dense layer has sufficient mechanical properties, and avoid the failure and peeling of the dense layer under thermal shock conditions. Compared with the preparation of environmental barriers or thermal / environmental barrier coatings by spraying and other methods in Chinese patents CN202110573926.X, the present invention forms the mixed dense layer in situ on the surface during the preparation of the ceramic-based composite material, and does not require subsequent coating treatment of the composite material, saving production costs. In addition, the mixed dense layer formed on the surface of the ceramic-based composite material by the method of the present invention improves the resistance of the ceramic-based composite material to water and oxygen corrosion (high-temperature water and oxygen corrosion) and thermal insulation, while avoiding the formation of low bonding strength interfaces between the coating / substrate and the coating / coating, effectively preventing interface cracking and coating peeling caused by incompatible thermal expansion coefficients in the coating system, and effectively extending the protection time.

[0025] (2) The present invention mixes a large amount of submicron ceramic powder into the PCS precursor, and then uses SiO 2The method of in-situ formation of silicate products by melt infiltration treatment can realize a large amount of uniform dispersion distribution of water-oxygen corrosion-resistant and high thermal insulation components in an area of ​​a certain thickness. By introducing high thermal insulation components, the temperature of the water-oxygen corrosion-resistant components during service is reduced, and the premature failure of the water-oxygen corrosion-resistant components at higher service temperatures is avoided, further extending the service life of ceramic-based composite materials with both water-oxygen corrosion resistance and high thermal insulation performance. However, Chinese patent CN202410315852.3 introduces water vapor corrosion-resistant components after the ceramic-based composite material has a high degree of densification. The pores of the composite material are relatively small, and the introduction is relatively difficult. At the same time, it can only play a single anti-water vapor corrosion effect. The present invention introduces ceramic powder into the ceramic-based composite material after the initial densification, that is, when the density is relatively low. The introduction difficulty is relatively low, and the filling effect on the pores of the composite material is better. After melt infiltration, the ceramic powder is introduced into the ceramic-based composite material with SiO 2 More anti-water and oxygen corrosion components and high thermal insulation components are formed in situ, so that the composite material has better anti-water and oxygen corrosion and high-temperature thermal insulation performance. In addition, the present invention realizes the gradient distribution of anti-water and oxygen corrosion components and high thermal insulation components by preparing a gradient concentration precursor solution, and can adjust the content of each component according to the service environment, design and optimize the anti-water and oxygen corrosion and thermal insulation performance, and better match and meet the service requirements.

[0026] Instruction Manual

[0027] The drawings of the present invention are provided for illustrative purposes only, and the proportions and sizes of the layers in the drawings may not necessarily be consistent with the actual products.

[0028] Figure 1 It is a schematic diagram of the cross-sectional structure of a ceramic-based composite material having both water-oxygen corrosion resistance and high thermal insulation performance prepared in some specific embodiments of the present invention.

[0029] In the figure: 1: High thermal insulation component: ZrSiO 4 Mg 2 SiO 4 ; 2: Anti-water corrosion component: Yb 2 SiO 5 、TiSiO 4 、HfSiO 4 ; 3: SiC and SiO 2 Matrix; 4: Ceramic fiber skeleton; 5: Ceramic matrix composite material. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] In a first aspect, the present invention provides a method for preparing a ceramic-based composite material having both water-oxygen corrosion resistance and high thermal insulation performance, the method comprising the following steps:

[0032] (1) Preparing porous ceramic matrix composite materials (also referred to as porous low-density ceramic matrix composite materials);

[0033] (2) Using polycarbosilane solution (PCS solution) as an impregnation liquid, the porous ceramic-based composite material is densified by a precursor impregnation pyrolysis process (i.e., PIP process) to obtain a preliminary densified ceramic-based composite material; the present invention does not specifically limit the densification process conditions using polycarbosilane solution as an impregnation liquid and the PIP process, and those skilled in the art can make conventional selections. Preferably, the PIP process is repeated multiple times to obtain a density of 1.3 to 1.5 g / cm 3 Initial densification of ceramic matrix composites;

[0034] (3) preparing n precursor impregnation solutions (also referred to as polycarbosilane precursor impregnation solutions) with gradient concentrations, each of which contains a solid component A, a solid component B and a polycarbosilane solution (PCS precursor solution), wherein the solid component A contains ytterbium oxide powder (Yb 2 O 3 Powder), titanium oxide powder (titanium dioxide TiO 2 powder) and hafnium oxide powder (HfO 2 Powder), the solid component B comprises zirconium oxide powder (zirconium dioxide ZrO 2 powder) and magnesium oxide powder (MgO powder); in some specific embodiments, the precursor impregnation liquid is composed of solid component A, solid component B and polycarbosilane solution, and each precursor impregnation liquid contains different contents of solid component A and solid component B; in the present invention, for example, a large amount of submicron Yb 2 O 3 、TiO 2 , HfO 2 、ZrO 2and MgO powder, PCS and xylene to obtain n PCS precursor impregnation solutions with gradient concentrations; when preparing the precursor impregnation solution, for example, the solid component A and the solid component B can be uniformly dispersed in the PCS precursor solution by stirring and / or ball milling;

[0035] (4) densifying the preliminarily densified ceramic matrix composite material by a precursor impregnation pyrolysis process (PIP process) in sequence with n gradient concentrations of precursor impregnation solutions to obtain a ceramic matrix composite material having a surface layer containing (rich in) solid component A and solid component B; wherein the content of solid component A in the surface layer decreases from the inside to the outside, and the content of solid component B in the surface layer increases from the inside to the outside; that is, in step (4) of the present invention, a Yb-rich ceramic matrix composite material is formed on the surface layer of the ceramic matrix composite material 2 O 3 、TiO 2 , HfO 2 、ZrO 2 and MgO regions, where Yb 2 O 3 、TiO 2 and HfO 2 The total content of ZrO decreases towards the surface. 2 The total content of MgO increases toward the surface; in the present invention, the direction from inside to outside is the direction toward the surface of the ceramic matrix composite material; in the present invention, the interior of the preliminarily densified ceramic matrix composite material is not easily impregnated with the precursor impregnation liquid in step (3), which can ensure that Yb-rich ... 2 O 3 、TiO 2 , HfO 2 、ZrO 2 and MgO regions, and the present invention densifies the porous ceramic-based composite material in step (2) to obtain a preliminary densified ceramic-based composite material, and this preliminary densification process is conducive to ensuring that the interior of the ceramic-based composite material has excellent mechanical properties; the present invention does not specifically limit the conditions of the PIP process using a precursor impregnation liquid containing solid component A, solid component B and polycarbosilane solution in step (4), and those skilled in the art can routinely select, preferably, for example, the same as the conditions of the PIP process using a polycarbosilane solution as an impregnation liquid;

[0036] (5) placing the ceramic-based composite material containing the solid component A and the solid component B on the surface into silicon dioxide powder for infiltration reaction to obtain a ceramic-based composite material having both water and oxygen corrosion resistance and high thermal insulation performance; that is, in step (5) of the present invention, silicon dioxide (SiO 2) powder as a reaction source, and the ceramic matrix composite material containing solid component A and solid component B on the surface is melt-infiltrated. SiO 2 With Yb 2 O 3 、TiO 2 and HfO 2 In-situ reaction forms ytterbium silicate (Yb 2 SiO 5 ), titanium silicate (TiSiO 4 ) and hafnium silicate (HfSiO 4 ), SiO 2 With ZrO 2 In situ reaction with MgO forms zirconium silicate (ZrSiO 4 ) and magnesium silicate (Mg 2 SiO 4 ), and finally a certain thickness of Yb is formed on the surface of the ceramic matrix composite material. 2 SiO 5 、TiSiO 4 、HfSiO 4 、ZrSiO 4 Mg 2 SiO 4 , SiC and SiO 2 matrix, and a mixed dense layer of fiber skeleton, in which Yb 2 SiO 5 、TiSiO 4 and HfSiO 4 The total content of ZrSiO 4 and Mg 2 SiO 4 The total content of MgO increases towards the surface.

[0037] The present invention prepares Yb in a certain thickness area on the surface of the composite material 2 SiO 5 、TiSiO 4 、HfSiO 4 、ZrSiO 4 Mg 2 SiO 4 , SiC and SiO 2 matrix, and a mixed dense layer of fiber skeleton; the present invention finds that Yb 2 SiO 5 、TiSiO 4 With good high temperature phase stability and excellent high temperature water corrosion resistance, HfSiO 4It has extremely high resistance to high temperature oxidation and excellent resistance to oxidation corrosion, and can provide composite materials with better resistance to high temperature water vapor corrosion; ZrSiO 4 and Mg 2 SiO 4 It has good phase stability and thermophysical properties, has the advantages of low sintering rate and low thermal conductivity, and can provide excellent thermal insulation for composite materials; molten SiO 2 It can further fill the pores on the surface of the composite material, prevent oxygen from diffusing along the pores to the core, and prevent the core from oxidizing; the fiber skeleton can effectively ensure that the mixed dense layer has sufficient mechanical properties, and avoid the failure and peeling of the dense layer under thermal shock conditions. Compared with the preparation of environmental barriers or thermal / environmental barrier coatings by spraying and other methods in Chinese patents CN202110573926.X, the present invention forms the mixed dense layer in situ on the surface during the preparation of the ceramic-based composite material, and does not require subsequent coating treatment of the composite material, saving production costs. In addition, the mixed dense layer formed on the surface of the ceramic-based composite material by the method of the present invention improves the resistance of the ceramic-based composite material to water and oxygen corrosion (high-temperature water and oxygen corrosion) and thermal insulation, while avoiding the generation of low bonding strength interfaces between the coating / substrate and the coating / coating, effectively preventing interface cracking and coating peeling caused by incompatible thermal expansion coefficients in the coating system, and effectively extending the protection time, that is, the anti-water and oxygen corrosion component and the high thermal insulation component in the present invention have higher bonding strength, better protection effect, and better service life.

[0038] The present invention mixes a large amount of submicron ceramic powder into the PCS precursor, and then uses SiO 2 The method of in-situ formation of silicate products by melt infiltration treatment can realize a large amount of uniform dispersion distribution of water-oxygen corrosion-resistant and high thermal insulation components in an area of ​​a certain thickness. By introducing high thermal insulation components, the temperature of the water-oxygen corrosion-resistant components during service is reduced, and the premature failure of the water-oxygen corrosion-resistant components at higher service temperatures is avoided, further extending the service life of ceramic-based composite materials with both water-oxygen corrosion resistance and high thermal insulation performance. However, Chinese patent CN202410315852.3 introduces water vapor corrosion-resistant components after the ceramic-based composite material has a high degree of densification. The pores of the composite material are relatively small, and the introduction is relatively difficult. At the same time, it can only play a single anti-water vapor corrosion effect. The present invention introduces ceramic powder into the ceramic-based composite material after the initial densification, that is, when the density is relatively low. The introduction difficulty is relatively low, and the filling effect on the pores of the composite material is better. After melt infiltration, the ceramic powder is introduced into the ceramic-based composite material with SiO 2More anti-water and oxygen corrosion components and high thermal insulation components are formed in situ, so that the composite material has better anti-water and oxygen corrosion and high-temperature thermal insulation performance. In addition, the present invention realizes the gradient distribution of anti-water and oxygen corrosion components and high thermal insulation components by preparing a gradient concentration precursor solution, and can adjust the content of each component according to the service environment, design and optimize the anti-water and oxygen corrosion and thermal insulation performance, and better match and meet the service requirements.

[0039] According to some preferred embodiments, in the precursor impregnation solutions (polycarbosilane precursor impregnation solutions) with n gradient concentrations, the content (mass percentage) of the solid component A contained therein shows a decreasing trend, and the content (mass percentage) of the solid component B contained therein shows an increasing trend; n ≥ 2 and n is a positive integer; in the present invention, different contents of the solid component A, the solid component B and the PCS solution are mixed to prepare n gradient concentration precursor impregnation solutions; the concentration range of the solid component A in the n gradient concentration precursor impregnation solutions is 1 0-50wt% (e.g., 10wt%, 20wt%, 30wt%, 40wt% or 50wt%), the concentration range of the solid component B in the precursor impregnation solution with n gradient concentrations is 10-50wt% (e.g., 10wt%, 20wt%, 30wt%, 40wt% or 50wt%); and / or the surface layer of the ceramic-based composite material with both water-oxygen corrosion resistance and high thermal insulation performance is composed of ytterbium silicate, titanium silicate, hafnium silicate, zirconium silicate, magnesium silicate, silicon carbide (SiC) and silicon dioxide (SiO 2 ) matrix, and a mixed dense layer of the fiber skeleton (also recorded as a mixed dense layer with water-oxygen corrosion resistance and high thermal insulation performance), wherein the total content (total mass percentage) of ytterbium silicate, titanium silicate and hafnium silicate in the surface layer decreases from the inside to the outside, and the total content (total mass percentage) of zirconium silicate and magnesium silicate in the surface layer increases from the inside to the outside; in the present invention, ytterbium silicate, titanium silicate and hafnium silicate constitute the water-oxygen corrosion resistance component (also recorded as the water vapor corrosion resistance component), and zirconium silicate and magnesium silicate constitute the high thermal insulation component.

[0040] According to some preferred embodiments, in step (1): the porous ceramic-based composite material is obtained by depositing an interface layer on the fibers of a fiber braid, the porous ceramic-based composite material has a fiber braid as a skeleton, the fibers can be carbon fibers or silicon carbide fibers, the braiding method can be any one of acupuncture or stitching, and the fibers of the fiber braid have an interface layer deposited by chemical vapor deposition (CVD) and the like, and the types of the interface layer include but are not limited to one or more of pyrolytic carbon (PyC), silicon carbide (SiC) or boron nitride (BN); preferably, the fiber braid is a carbon fiber braid or a silicon carbide fiber braid; preferably, the density of the fiber braid is 0.4 to 0.7 g / cm 3(e.g. 0.4, 0.45, 0.5, 0.55, 0.6, 0.65 or 0.7 g / cm 3 ); The present invention does not specifically limit the source of the fiber braid, and can be directly purchased products or prepared by existing methods; preferably, the interface layer is one or more of a pyrolytic carbon interface layer, a silicon carbide interface layer or a boron nitride interface layer; preferably, the density of the porous ceramic-based composite material is 0.8-1.2 g / cm 3 (e.g. 0.8, 0.9, 1.0, 1.1 or 1.2 g / cm 3 ); The present invention does not specifically limit the process conditions for depositing the interface layer, which is a conventional technique in the art. Preferably, the density of the porous ceramic-based composite material after depositing the interface layer is 0.8 to 1.2 g / cm 3 That's it.

[0041] According to some preferred embodiments, in step (2): the polycarbosilane solution is a xylene solution of polycarbosilane, preferably, the mass fraction of polycarbosilane contained in the polycarbosilane solution is 35-60% (for example, 35%, 40%, 45%, 50%, 55% or 60%); and / or the PIP process is repeated multiple times until a density of 1.3-1.5 g / cm is obtained. 3 Preliminary densification of ceramic matrix composites.

[0042] According to some preferred embodiments, in step (3): the precursor impregnation solution is composed of a solid component A, a solid component B and a polycarbosilane solution, the polycarbosilane solution is a xylene solution of polycarbosilane, preferably, the mass fraction of polycarbosilane in the polycarbosilane solution is 10 to 30 wt% (e.g., 10 wt%, 15 wt%, 20 wt%, 25 wt% or 30 wt%); the particle size D50 of the ytterbium oxide powder, the titanium oxide powder and / or the hafnium oxide powder is 0.1 μm to 1 μm ( For example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1 μm); and / or the solid component A contains 40-60% (for example, 40%, 45%, 50%, 55% or 60%) of ytterbium oxide powder, 20-30% (for example, 20%, 22%, 24%, 26%, 28% or 30%) of titanium oxide powder and 20-30% (for example, 20%, 22%, 24%, 26%, 28% or 30%) of hafnium oxide powder by mass fraction.

[0043] The solid component A in the present invention is obtained by controlling the ytterbium oxide (Yb 2 O 3 ), titanium oxide (TiO 2 ) and hafnium oxide (HfO 2) has a suitable mass fraction and reacts with silicon dioxide in situ to generate ytterbium silicate (Yb 2 SiO 5 ), titanium silicate (TiSiO 4 ) and hafnium silicate (HfSiO 4 ) is composed of an optimized structure that is resistant to high-temperature water and oxygen corrosion. The balanced distribution of each component ensures the compactness, uniformity and high-temperature stability of the silicate layer, which is beneficial to prevent further penetration and erosion of water vapor and oxygen and improve the Yb 2 SiO 5 、TiSiO 4 and HfSiO 4 The coordination of these silicates at high temperatures helps to further enhance the ability to resist water and oxygen corrosion, thereby achieving excellent resistance to high-temperature water and oxygen corrosion. The present invention finds that if the content of ytterbium oxide powder in the solid component A is too low, the generated Yb 2 SiO 5 If the content of ytterbium oxide powder in solid component A is too high, the integrity and sealing of the protective layer will be insufficient, thereby weakening the ability to resist water and oxygen corrosion. 2 SiO 5 If the content of titanium oxide in the solid component A is too low, the internal stress in the protective layer will be large, and it will fail prematurely under high temperature conditions. 4 If the content of titanium oxide in the solid component A is too high, the generated TiSiO 4 If the content of hafnium oxide in solid component A is too low, HfSiO 4 If the content is insufficient, the oxidation resistance and thermal stability of the material will be weakened, thereby reducing the synergistic anti-water and oxygen corrosion performance; if the hafnium oxide content in the solid component A is too high, it will greatly increase the preparation cost and also reduce the Yb 2 SiO 5 and TiSiO 4 The amount of formation will also reduce the overall mechanical properties of the water vapor corrosion resistance layer.

[0044] According to some preferred embodiments, in step (3): the particle size D50 of the zirconium oxide powder and / or the magnesium oxide powder is 0.1 μm to 1 μm (for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1 μm); the solid component B contains 40 to 60% (for example, 40%, 45%, 50%, 55% or 60%) of zirconium oxide powder and 40 to 60% (for example, 40%, 45%, 50%, 55% or 60%) of magnesium oxide powder by mass fraction; in the present invention, preferably, the solid component B contains 40 to 60% of zirconium oxide powder and 40 to 60% of magnesium oxide powder by mass fraction, and the solid component B forms a zirconium silicate (ZrSiO 4 ) and magnesium silicate (Mg 2 SiO 4 ) composed of a high thermal insulation component, the present invention found that the thermal insulation performance of the high thermal insulation component is better than that of a single zirconium silicate (ZrSiO 4 ) or single magnesium silicate (Mg 2 SiO 4 ) is better, because ZrSiO 4 and Mg 2 SiO 4 With different crystal structures and thermal expansion coefficients, the multiphase structure formed can scatter heat flow at the grain boundaries, which can effectively reduce the overall thermal conductivity of the material. 4 and Mg 2 SiO 4 Each of them has excellent high temperature resistance and thermal insulation. The composite structure can remain stable in a high temperature environment and delay the penetration of heat. Their combination not only has the advantages of both materials, but also utilizes the synergistic effect between the materials to significantly improve the thermal insulation performance. In addition, the present invention finds that compared with the coating of Yb-doped Gd 2 Zr 2 O 7 Thermal insulation layer, ZrSiO 4 and Mg 2 SiO 4 The thermal expansion coefficient of the high insulation component is lower, the thermal mismatch stress between it and the ceramic matrix composite material is lower, and it is not easy to crack. 4 and Mg 2 SiO 4 It has better compatibility with ceramic-based composite materials and can maintain thermal insulation effects for a longer period of time.

[0045] According to some preferred embodiments, in step (4): the thickness of the solid component A and the solid component B in the ceramic-based composite material containing the solid component A and the solid component B on the surface is 500 to 2000 μm (e.g., 500, 750, 1000, 1250, 1500, 1750 or 2000 μm); that is, the present invention uses a gradient concentration precursor impregnation solution to perform subsequent densification on the preliminarily densified ceramic-based composite material through a PIP process, and forms a Yb-rich ceramic-based composite material on the surface of the ceramic-based composite material. 2 O 3 、TiO 2 , HfO 2 、ZrO 2 and MgO regions, where Yb 2 O 3 、TiO 2 and HfO 2 The total content of ZrO decreases towards the surface. 2 The total content of MgO increases toward the surface, and the thickness of this area is 500-2000 μm; and / or the density of the ceramic-based composite material containing solid component A and solid component B on the surface is 1.8-2.1 g / cm 3 .

[0046] According to some preferred embodiments, in step (5): the particle size D50 of the silica powder is 0.1 μm to 1 μm (for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1 μm); the temperature of the infiltration reaction is 1400 to 1700°C (for example, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C, 1650°C or 1700°C), the time of the infiltration reaction is 60 to 180 min (for example, 60, 90, 120, 150 or 180 min); and / or the heating rate to the temperature of the infiltration reaction is 2 to 4°C / min (for example, 2, 2.5, 3, 3.5 or 4°C / min).

[0047] According to some preferred embodiments, in step (5): the thickness of the mixed dense layer is 500-2000 μm (e.g., 500, 750, 1000, 1250, 1500, 1750 or 2000 μm); the density of the ceramic-based composite material having both water-oxygen corrosion resistance and high thermal insulation performance is 2.2-2.5 g / cm 3 The ceramic-based composite material having both water-oxygen corrosion resistance and high thermal insulation performance has a thermal conductivity of no more than 5 W / m·K at 1500°C and has excellent water-oxygen corrosion resistance at 1200-1500°C. Specifically, the ceramic-based composite material having both water-oxygen corrosion resistance and high thermal insulation performance in the present invention contains 90 vol.% water (H 2O) and 10 vol.% oxygen (O 2 The weight loss rate of the product under water-oxygen corrosion conditions for 100 hours is not more than 0.5 mg / cm 2 , i.e. at 1500℃, 90H 2 O-10O 2 The weight loss rate under water-oxygen corrosion conditions for 100h is no more than 0.5mg / cm 2 ; In the present invention, "vol.%" means volume percentage.

[0048] In a second aspect, the present invention provides a ceramic-based composite material having both water-oxygen corrosion resistance and high thermal insulation performance, which is prepared by the preparation method described in the first aspect of the present invention. Compared with the prior art, the ceramic-based composite material prepared by the present invention has both water-oxygen corrosion resistance and high thermal insulation performance, and the combination strength of water-oxygen corrosion resistance and high thermal insulation components is higher, the protective effect is better, and the service life is better.

[0049] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments. The present invention may also have other various embodiments, and those skilled in the art may make various corresponding changes and deformations according to the present invention without departing from the spirit and essence of the present invention, but these corresponding changes and deformations shall all belong to the protection scope of the claims attached to the present invention.

[0050] Example 1

[0051] ① Preparation of porous ceramic matrix composite materials: Using carbon fiber as the skeleton, a needle-punched weaving method was used to obtain a density of 0.5g / cm 3 A carbon fiber braid is formed by depositing a pyrolytic carbon interface layer on the carbon fibers of the carbon fiber braid by chemical vapor deposition to obtain a carbon fiber with a density of 0.9 g / cm 3 porous ceramic matrix composites.

[0052] ② Preliminary densification process: PCS solution (polycarbosilane solution) was used as the precursor impregnation solution to densify the SiC matrix of the porous ceramic-based composite material obtained in step ① through the PIP process. The PIP process was repeated 3 times to obtain a density of 1.4 g / cm 3 The polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 55%.

[0053] ③Prepare precursor impregnation solutions with gradient concentrations: prepare two precursor impregnation solutions with gradient concentrations, each of which is composed of a solid component A, a solid component B and a polycarbosilane solution, wherein the solid component A is composed of Yb 2 O 3Powder 50wt%, TiO 2 Powder 25wt% and HfO 2 The powder is composed of 25wt%, the Yb 2 O 3 Powder, the TiO 2 Powder and the HfO 2 The particle size D50 of the powder is 0.5 μm. The solid component B is composed of ZrO 2 powder 50wt% and MgO powder 50wt%, the ZrO 2 The particle size D50 of the powder and the MgO powder are both 0.5 μm. In the two precursor impregnation solutions with gradient concentrations, the polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane is 20%; one precursor impregnation solution contains a solid component A with a mass fraction of 40% and a solid component B with a mass fraction of 20%, and the other precursor impregnation solution contains a solid component A with a mass fraction of 20% and a solid component B with a mass fraction of 40%.

[0054] ④ Subsequent densification process: The preliminary densified ceramic matrix composite material obtained in step ② is subsequently densified by the PIP process using the two gradient concentration precursor impregnation solutions prepared in step ③ to obtain a ceramic matrix composite material rich in solid component A and solid component B on the surface, and a Yb-rich surface is formed. 2 O 3 、TiO 2 , HfO 2 、ZrO 2 and the thickness of the MgO region is about 1000 μm; when performing the PIP process in step ④, firstly, a precursor impregnation liquid containing a mass fraction of 40 wt% of solid component A and a mass fraction of 20 wt% of solid component B is used as an impregnation liquid for 4 rounds of PIP process, and then a precursor impregnation liquid containing a mass fraction of 20 wt% of solid component A and a mass fraction of 40 wt% of solid component B is used as an impregnation liquid for 4 rounds of PIP process, so that the content of solid component A in the surface layer decreases from the inside to the outside, and the content of solid component B in the surface layer increases from the inside to the outside; after this process, a density of 2.0 g / cm 3 The surface layer of the ceramic matrix composite material is rich in solid component A and solid component B.

[0055] ⑤Silica infiltration process: The ceramic matrix composite material with a surface layer rich in solid component A and solid component B obtained in step ④ is placed on SiO 2The powder (particle size D50 is 0.5 μm) was subjected to a melt infiltration reaction at a temperature of 1650°C for 120 min and a heating rate of 3°C / min to obtain a density of 2.39 g / cm 3 A ceramic-based composite material with both water-oxygen corrosion resistance and high thermal insulation performance, wherein the surface layer of the ceramic-based composite material with both water-oxygen corrosion resistance and high thermal insulation performance is a mixed dense layer composed of ytterbium silicate, titanium silicate, hafnium silicate, zirconium silicate, magnesium silicate, silicon carbide and silicon dioxide matrix, and a fiber skeleton, and the thickness of the mixed dense layer is about 1000 μm, wherein the total content of ytterbium silicate, titanium silicate and hafnium silicate in the surface layer decreases from the inside to the outside, and the total content of zirconium silicate and magnesium silicate in the surface layer increases from the inside to the outside.

[0056] Performance test: The ceramic matrix composite material prepared in this embodiment has both water and oxygen corrosion resistance and high thermal insulation performance at 1500°C, 90H 2 O-10O 2 The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 0.36mg / cm 2 The thermal conductivity of the prepared ceramic matrix composite material at 1500°C is 3.2W / (m·K).

[0057] Example 2

[0058] Embodiment 2 is substantially the same as Embodiment 1, except that:

[0059] ① Preparation of porous ceramic matrix composites: Silicon carbide fiber was used as the skeleton and the suture weaving method was used to obtain a density of 0.55g / cm 3 The silicon carbide fiber braid is a pyrolytic carbon interfacial layer deposited on the silicon carbide fibers of the silicon carbide fiber braid by chemical vapor deposition to obtain a density of 0.97 g / cm 3 porous ceramic matrix composites.

[0060] ② Preliminary densification process: PCS solution (polycarbosilane solution) was used as the precursor impregnation solution to densify the SiC matrix of the porous ceramic-based composite material obtained in step ① through the PIP process. The PIP process was repeated three times to obtain a density of 1.48 g / cm 3 The polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 55%.

[0061] ③Prepare precursor impregnation solutions with gradient concentrations: prepare two precursor impregnation solutions with gradient concentrations, each of which is composed of a solid component A, a solid component B and a polycarbosilane solution, wherein the solid component A is composed of Yb2 O 3 Powder 50wt%, TiO 2 Powder 25wt% and HfO 2 The powder is composed of 25wt%, the Yb 2 O 3 Powder, the TiO 2 Powder and the HfO 2 The particle size D50 of the powder is 0.5 μm. The solid component B is composed of ZrO 2 powder 50wt% and MgO powder 50wt%, the ZrO 2 The particle size D50 of the powder and the MgO powder are both 0.5μm. In the two gradient concentration precursor impregnation solutions, the polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane is 20%; one precursor impregnation solution contains a solid component A with a mass fraction of 30wt%, and a solid component B with a mass fraction of 15wt%, and the other precursor impregnation solution contains a solid component A with a mass fraction of 15wt%, and a solid component B with a mass fraction of 30wt%.

[0062] ④ Subsequent densification process: The preliminary densified ceramic matrix composite material obtained in step ② is subsequently densified by the PIP process using the two gradient concentration precursor impregnation solutions prepared in step ③ to obtain a ceramic matrix composite material rich in solid component A and solid component B on the surface, and a Yb-rich surface is formed. 2 O 3 、TiO 2 , HfO 2 、ZrO 2 and the thickness of the MgO region is about 1000 μm; when performing the PIP process in step ④, firstly, a precursor impregnation liquid containing a mass fraction of 30 wt% of solid component A and a mass fraction of 15 wt% of solid component B is used as an impregnation liquid for 4 rounds of PIP process, and then a precursor impregnation liquid containing a mass fraction of 15 wt% of solid component A and a mass fraction of 30 wt% of solid component B is used as an impregnation liquid for 4 rounds of PIP process, so that the content of solid component A in the surface layer decreases from the inside to the outside, and the content of solid component B in the surface layer increases from the inside to the outside; after this process, a density of 2.04 g / cm 3 The surface layer of the ceramic matrix composite material is rich in solid component A and solid component B.

[0063] After the subsequent silicon dioxide infiltration process, the density of the ceramic matrix composite material with both water and oxygen corrosion resistance and high thermal insulation performance is 2.23 g / cm 3 .

[0064] Performance test: The ceramic matrix composite material prepared in this embodiment has both water and oxygen corrosion resistance and high thermal insulation performance at 1500°C, 90H 2 O-10O 2 The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 0.41mg / cm 2 The thermal conductivity of the prepared ceramic matrix composite material is 4.6W / (m·K) at 1500℃.

[0065] Example 3

[0066] Embodiment 3 is substantially the same as Embodiment 1, except that:

[0067] ① Preparation of porous ceramic matrix composite materials: Using carbon fiber as the skeleton, a needle-punched weaving method was used to obtain a density of 0.45g / cm 3 A carbon fiber braid is formed by depositing a pyrolytic carbon interface layer on the carbon fibers of the carbon fiber braid by chemical vapor deposition to obtain a carbon fiber with a density of 0.82 g / cm 3 porous ceramic matrix composites.

[0068] ② Preliminary densification process: PCS solution (polycarbosilane solution) was used as the precursor impregnation solution to densify the SiC matrix of the porous ceramic-based composite material obtained in step ① through the PIP process. The PIP process was repeated 3 times to obtain a density of 1.33 g / cm 3 The polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 40%.

[0069] ④ Subsequent densification process: The preliminary densified ceramic matrix composite material obtained in step ② is subsequently densified by the PIP process using the two gradient concentration precursor impregnation solutions prepared in step ③ to obtain a ceramic matrix composite material rich in solid component A and solid component B on the surface, and a Yb-rich surface is formed. 2 O 3 、TiO 2 , HfO 2 、ZrO 2 and the thickness of the MgO region is about 1500 μm; when performing the PIP process in step ④, firstly, a precursor impregnation liquid containing a mass fraction of 40 wt% of solid component A and a mass fraction of 20 wt% of solid component B is used as an impregnation liquid for 4 rounds of PIP process, and then a precursor impregnation liquid containing a mass fraction of 20 wt% of solid component A and a mass fraction of 40 wt% of solid component B is used as an impregnation liquid for 4 rounds of PIP process, so that the content of solid component A in the surface layer decreases from the inside to the outside, and the content of solid component B in the surface layer increases from the inside to the outside; after this process, a density of 2.11 g / cm3 The surface layer of the ceramic matrix composite material is rich in solid component A and solid component B.

[0070] ⑤Silica infiltration process: The ceramic matrix composite material with a surface layer rich in solid component A and solid component B obtained in step ④ is placed on SiO 2 The powder (particle size D50 is 0.5 μm) was subjected to a melt infiltration reaction at a temperature of 1700°C for 120 min and a heating rate of 3°C / min to obtain a density of 2.48 g / cm 3 A ceramic-based composite material with both water-oxygen corrosion resistance and high thermal insulation performance, wherein the surface layer of the ceramic-based composite material with both water-oxygen corrosion resistance and high thermal insulation performance is a mixed dense layer composed of ytterbium silicate, titanium silicate, hafnium silicate, zirconium silicate, magnesium silicate, silicon carbide and silicon dioxide matrix, and a fiber skeleton, and the thickness of the mixed dense layer is about 1500μm, wherein the total content of ytterbium silicate, titanium silicate and hafnium silicate in the surface layer decreases from the inside to the outside, and the total content of zirconium silicate and magnesium silicate in the surface layer increases from the inside to the outside.

[0071] Performance test: The ceramic matrix composite material prepared in this embodiment has both water and oxygen corrosion resistance and high thermal insulation performance at 1500°C, 90H 2 O-10O 2 The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 0.24mg / cm 2 The thermal conductivity of the prepared ceramic matrix composite material at 1500℃ is 2.6W / (m·K).

[0072] Example 4

[0073] Embodiment 4 is substantially the same as Embodiment 1, except that:

[0074] ① Preparation of porous ceramic matrix composite materials: Using carbon fiber as the skeleton, a needle-punched weaving method was used to obtain a density of 0.5g / cm 3 A carbon fiber braid is formed by depositing a boron nitride interface layer on the carbon fibers of the carbon fiber braid by chemical vapor deposition to obtain a carbon fiber braid with a density of 1.02 g / cm 3 porous ceramic matrix composites.

[0075] ② Preliminary densification process: PCS solution (polycarbosilane solution) was used as the precursor impregnation solution to densify the SiC matrix of the porous ceramic-based composite material obtained in step ① through the PIP process. The PIP process was repeated three times to obtain a density of 1.34 g / cm 3 The polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 55%.

[0076] ④ Subsequent densification process: The preliminary densified ceramic matrix composite material obtained in step ② is subsequently densified by the PIP process using the two gradient concentration precursor impregnation solutions prepared in step ③ to obtain a ceramic matrix composite material rich in solid component A and solid component B on the surface, and a Yb-rich surface is formed. 2 O 3 、TiO 2 , HfO 2 、ZrO 2 and the thickness of the MgO region is about 1000 μm; when performing the PIP process in step ④, firstly, a precursor impregnation liquid containing a mass fraction of 40 wt% of solid component A and a mass fraction of 20 wt% of solid component B is used as an impregnation liquid for 4 rounds of PIP process, and then a precursor impregnation liquid containing a mass fraction of 20 wt% of solid component A and a mass fraction of 40 wt% of solid component B is used as an impregnation liquid for 4 rounds of PIP process, so that the content of solid component A in the surface layer decreases from the inside to the outside, and the content of solid component B in the surface layer increases from the inside to the outside; after this process, a density of 1.94 g / cm 3 The surface layer of the ceramic matrix composite material is rich in solid component A and solid component B.

[0077] ⑤Silica infiltration process: The ceramic matrix composite material with a surface layer rich in solid component A and solid component B obtained in step ④ is placed on SiO 2 The powder (particle size D50 is 0.5 μm) was subjected to infiltration reaction at a temperature of 1500°C for 90 min and a heating rate of 3°C / min to obtain a density of 2.29 g / cm 3 A ceramic-based composite material with both water-oxygen corrosion resistance and high thermal insulation performance, wherein the surface layer of the ceramic-based composite material with both water-oxygen corrosion resistance and high thermal insulation performance is a mixed dense layer composed of ytterbium silicate, titanium silicate, hafnium silicate, zirconium silicate, magnesium silicate, silicon carbide and silicon dioxide matrix, and a fiber skeleton, and the thickness of the mixed dense layer is about 800 μm, wherein the total content of ytterbium silicate, titanium silicate and hafnium silicate in the surface layer decreases from the inside to the outside, and the total content of zirconium silicate and magnesium silicate in the surface layer increases from the inside to the outside.

[0078] Performance test: The ceramic matrix composite material prepared in this embodiment has both water and oxygen corrosion resistance and high thermal insulation performance at 1500°C, 90H 2 O-10O 2 The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 0.42mg / cm 2The thermal conductivity of the prepared ceramic matrix composite material is 4.7W / (m·K) at 1500℃.

[0079] Example 5

[0080] Example 5 is substantially the same as Example 1, except that:

[0081] In step ③, the Yb 2 O 3 Powder, the TiO 2 Powder and the HfO 2 The particle size D50 of the powder is 0.1 μm. 2 The particle size D50 of the powder and the MgO powder is both 0.1 μm.

[0082] In step ④, the surface layer forms a Yb-rich 2 O 3 、TiO 2 , HfO 2 、ZrO 2 The thickness of the MgO region is about 1500 μm, and the density of the ceramic matrix composite material rich in solid component A and solid component B is 2.05 g / cm 3 .

[0083] In step ⑤, the SiO 2 The particle size D50 of the powder is 0.1 μm; after the silicon dioxide infiltration process in step ⑤, the thickness of the mixed dense layer is about 1500 μm, and the density of the prepared ceramic-based composite material with both water and oxygen corrosion resistance and high thermal insulation performance is 2.46 g / cm 3 .

[0084] Performance test: The ceramic matrix composite material prepared in this embodiment has both water and oxygen corrosion resistance and high thermal insulation performance at 1500°C, 90H 2 O-10O 2 The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 0.31mg / cm 2 The thermal conductivity of the prepared ceramic matrix composite material at 1500℃ is 2.9W / (m·K).

[0085] Example 6

[0086] Embodiment 6 is substantially the same as Embodiment 1, except that:

[0087] ③Prepare precursor impregnation solutions with gradient concentrations: prepare two precursor impregnation solutions with gradient concentrations, each of which is composed of a solid component A, a solid component B and a polycarbosilane solution, wherein the solid component A is composed of Yb 2 O 3Powder 40wt%, TiO 2 Powder 30wt% and HfO 2 The powder is composed of 30wt%, the Yb 2 O 3 Powder, the TiO 2 Powder and the HfO 2 The particle size D50 of the powder is 0.5 μm. The solid component B is composed of ZrO 2 powder 50wt% and MgO powder 50wt%, the ZrO 2 The particle size D50 of the powder and the MgO powder are both 0.5μm; in the two gradient concentration precursor impregnation solutions, the polycarbosilane solution is a xylene solution of polycarbosilane, wherein the mass fraction of polycarbosilane is 20%; one precursor impregnation solution contains a solid component A with a mass fraction of 40% and a solid component B with a mass fraction of 20%, and the other precursor impregnation solution contains a solid component A with a mass fraction of 20% and a solid component B with a mass fraction of 40%.

[0088] In step ④, the density of the ceramic matrix composite material rich in solid component A and solid component B on the surface layer is 2.03 g / cm 3 .

[0089] After the silicon dioxide infiltration process in the subsequent step ⑤ of this embodiment, the density of the ceramic-based composite material with both water-oxygen corrosion resistance and high thermal insulation performance is 2.42 g / cm 3 .

[0090] Performance test: The ceramic matrix composite material prepared in this embodiment has both water and oxygen corrosion resistance and high thermal insulation performance at 1500°C, 90H 2 O-10O 2 The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 0.30mg / cm 2 The thermal conductivity of the prepared ceramic matrix composite material at 1500℃ is 3.1W / (m·K).

[0091] Example 7

[0092] Example 7 is substantially the same as Example 1, except that:

[0093] ③Prepare precursor impregnation solutions with gradient concentrations: prepare two precursor impregnation solutions with gradient concentrations, each of which is composed of a solid component A, a solid component B and a polycarbosilane solution, wherein the solid component A is composed of Yb 2 O 3 Powder 60wt%, TiO 2 Powder 20wt% and HfO 2The powder is composed of 20wt%, the Yb 2 O 3 Powder, the TiO 2 Powder and the HfO 2 The particle size D50 of the powder is 0.5 μm. The solid component B is composed of ZrO 2 powder 50wt% and MgO powder 50wt%, the ZrO 2 The particle size D50 of the powder and the MgO powder are both 0.5 μm. In the two gradient precursor impregnation solutions, the polycarbosilane solution is a xylene solution of polycarbosilane, wherein the mass fraction of polycarbosilane is 20%; one precursor impregnation solution contains a solid component A with a mass fraction of 40% and a solid component B with a mass fraction of 20%, and the other precursor impregnation solution contains a solid component A with a mass fraction of 20% and a solid component B with a mass fraction of 40%.

[0094] In step ④, the density of the ceramic matrix composite material rich in solid component A and solid component B on the surface layer is 1.95 g / cm 3 .

[0095] In this embodiment, after the subsequent step ⑤ of the silicon dioxide infiltration process, the density of the ceramic-based composite material with both water and oxygen corrosion resistance and high thermal insulation performance is 2.31 g / cm 3 .

[0096] Performance test: The ceramic matrix composite material prepared in this embodiment has both water and oxygen corrosion resistance and high thermal insulation performance at 1500°C, 90H 2 O-10O 2 The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 0.42mg / cm 2 The thermal conductivity of the prepared ceramic matrix composite material is 3.3W / (m·K) at 1500℃.

[0097] Comparative Example 1

[0098] Comparative Example 1 is substantially the same as Example 1, except that:

[0099] ③Prepare the precursor impregnation solution: The precursor impregnation solution is composed of solid component A, solid component B and polycarbosilane solution, wherein the solid component A is composed of Yb 2 O 3 Powder 50wt%, TiO 2 Powder 25wt% and HfO 2 The powder is composed of 25wt%, the Yb 2 O 3 Powder, the TiO 2Powder and the HfO 2 The particle size D50 of the powder is 0.5 μm. The solid component B is composed of ZrO 2 powder 50wt% and MgO powder 50wt%, the ZrO 2 The particle size D50 of the powder and the MgO powder are both 0.5μm. In the precursor impregnation solution, the polycarbosilane solution is a xylene solution of polycarbosilane, wherein the mass fraction of polycarbosilane is 20%; the mass fraction of solid component A contained in the precursor impregnation solution is 40%, and the mass fraction of solid component B contained in the precursor impregnation solution is 20%.

[0100] ④ Subsequent densification process: The preliminary densified ceramic matrix composite material obtained in step ② is subsequently densified by using the precursor impregnation solution prepared in step ③ through 8 rounds of PIP process to obtain a ceramic matrix composite material rich in solid component A and solid component B on the surface, and a Yb-rich surface is formed. 2 O 3 、TiO 2 , HfO 2 、ZrO 2 The thickness of the MgO region is about 1000 μm, and the density of the ceramic matrix composite material rich in solid component A and solid component B is 1.90 g / cm 3 .

[0101] After the silicon dioxide infiltration process in the subsequent step ⑤, the density of the ceramic matrix composite material obtained in this comparative example is 2.18 g / cm 3 .

[0102] Performance test: The ceramic matrix composite material prepared in this comparative example is tested at 1500℃, 90H 2 O-10O 2 The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 0.43mg / cm 2 The thermal conductivity of the prepared ceramic-based composite material at 1500°C is 10.7W / (m·K).

[0103] Comparative Example 2

[0104] Comparative Example 2 is substantially the same as Example 1, except that:

[0105] ③Prepare the precursor impregnation solution: The precursor impregnation solution is composed of solid component A, solid component B and polycarbosilane solution, wherein the solid component A is composed of Yb 2 O 3 Powder 50wt%, TiO 2 Powder 25wt% and HfO 2 The powder is composed of 25wt%, the Yb 2 O3 Powder, the TiO 2 Powder and the HfO 2 The particle size D50 of the powder is 0.5 μm. The solid component B is composed of ZrO 2 powder 50wt% and MgO powder 50wt%, the ZrO 2 The particle size D50 of the powder and the MgO powder are both 0.5μm. In the precursor impregnation solution, the polycarbosilane solution is a xylene solution of polycarbosilane, in which the mass fraction of polycarbosilane is 20%; a precursor impregnation solution contains a solid component A with a mass fraction of 20% and a solid component B with a mass fraction of 40%.

[0106] ④ Subsequent densification process: The preliminary densified ceramic matrix composite material obtained in step ② is subsequently densified by using the precursor impregnation solution prepared in step ③ through 8 rounds of PIP process to obtain a ceramic matrix composite material rich in solid component A and solid component B on the surface, and a Yb-rich surface is formed. 2 O 3 、TiO 2 , HfO 2 、ZrO 2 The thickness of the MgO region is about 1000 μm, and the density of the ceramic matrix composite material rich in solid component A and solid component B on the surface is 1.84 g / cm 3 .

[0107] After the subsequent step ⑤ of silicon dioxide infiltration, the density of the ceramic matrix composite material obtained in this comparative example is 2.07 g / cm 3 .

[0108] Performance test: The ceramic matrix composite material prepared in this comparative example is tested at 1500℃, 90H 2 O-10O 2 The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 2.9mg / cm 2 The thermal conductivity of the prepared ceramic-based composite material is 3.4 W / (m·K) at 1500°C.

[0109] Comparative Example 3

[0110] Comparative Example 3 is substantially the same as Example 1, except that:

[0111] ③Prepare the precursor impregnation solution: prepare the precursor impregnation solution, the precursor impregnation solution is composed of a solid component A and a polycarbosilane solution, and the solid component A is only Yb 2 O 3 Powder, the Yb 2 O 3The particle size D50 of the powder is 0.5 μm. The polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane contained in the polycarbosilane solution is 30%. The mass fraction of solid component A contained in the precursor impregnation solution is 40 wt%.

[0112] ④ Subsequent densification process: The pre-densified ceramic matrix composite material obtained in step ② was subsequently densified by 8 rounds of PIP process using the precursor impregnation solution prepared in step ③ to obtain a ceramic matrix composite material rich in solid component A on the surface with a density of 1.86 g / cm 3 .

[0113] ⑤Silica infiltration process: The ceramic matrix composite material with a surface rich in solid component A obtained in step ④ is placed in SiO 2 The powder (particle size D50 is 0.5 μm) is subjected to a melt infiltration reaction at a temperature of 1650°C for 120 min and a heating rate of 3°C / min to obtain a ceramic matrix composite material with a density of 2.02 g / cm 3 .

[0114] Performance test: The ceramic matrix composite material prepared in this comparative example is tested at 1500℃, 90H 2 O-10O 2 The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 0.75mg / cm 2 The thermal conductivity of the prepared ceramic-based composite material at 1500°C is 11.9W / (m·K).

[0115] Comparative Example 4

[0116] Comparative Example 4 is substantially the same as Example 1, except that:

[0117] ③Prepare the precursor impregnation solution: prepare the precursor impregnation solution, the precursor impregnation solution is composed of a solid component B and a polycarbosilane solution, the solid component B is ZrO 2 Powder, the ZrO 2 The particle size D50 of the powder is 0.5 μm. The polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane contained in the polycarbosilane solution is 30%. The mass fraction of solid component B contained in the precursor impregnation solution is 40 wt%.

[0118] ④ Subsequent densification process: The preliminary densified ceramic matrix composite material obtained in step ② was subsequently densified by 8 rounds of PIP process using the precursor impregnation solution prepared in step ③ to obtain a ceramic matrix composite material rich in solid component B on the surface with a density of 1.73 g / cm 3 .

[0119] ⑤Silica infiltration process: The ceramic matrix composite material with a surface rich in solid component B obtained in step ④ is placed in SiO 2 The powder (particle size D50 is 0.5 μm) is subjected to a melt infiltration reaction at a temperature of 1650°C for 120 min and a heating rate of 3°C / min to obtain a ceramic matrix composite material with a density of 1.99 g / cm 3 .

[0120] Performance test: The ceramic matrix composite material prepared in this comparative example is tested at 1500℃, 90H 2 O-10O 2 The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 4.8mg / cm 2 The thermal conductivity of the prepared ceramic-based composite material at 1500°C is 7.7W / (m·K).

[0121] Comparative Example 5

[0122] Comparative Example 5 is substantially the same as Example 1, except that:

[0123] ② Preliminary densification process: PCS solution (polycarbosilane solution) is used as the precursor impregnation solution to densify the SiC matrix of the porous ceramic-based composite material obtained in step ① through the PIP process. The PIP process is repeated several times until a density of 1.85 g / cm is obtained. 3 The polycarbosilane solution is a xylene solution of polycarbosilane, and the mass fraction of polycarbosilane in the polycarbosilane solution is 60%.

[0124] In step ④, the surface layer forms Yb 2 O 3 、TiO 2 , HfO 2 、ZrO 2 The thickness of the MgO region is about 300 μm, and the density of the ceramic matrix composite material containing solid component A and solid component B on the surface layer is 1.96 g / cm 3 .

[0125] In this comparative example, after the silicon dioxide infiltration process in the subsequent step ⑤, the thickness of the mixed dense layer is about 1500 μm, and the density of the obtained ceramic matrix composite material is 2.05 g / cm 3 .

[0126] Performance test: The ceramic matrix composite material prepared in this comparative example is tested at 1500℃, 90H 2 O-10O 2The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 6.8mg / cm 2 The thermal conductivity of the prepared ceramic-based composite material at 1500°C is 12.8W / (m·K).

[0127] Comparative Example 6

[0128] Comparative Example 6 is substantially the same as Example 1, except that:

[0129] The silicon dioxide infiltration process in step ⑤ is not included.

[0130] Performance test: The ceramic matrix composite material prepared in this comparative example is tested at 1500℃, 90H 2 O-10O 2 The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 14.7mg / cm 2 The thermal conductivity of the prepared ceramic matrix composite material at 1500℃ is 13.1W / (m·K).

[0131] Comparative Example 7

[0132] Comparative Example 7 is substantially the same as Example 1, except that:

[0133] ③Prepare precursor impregnation solutions with gradient concentrations: prepare two precursor impregnation solutions with gradient concentrations, each of which is composed of a solid component A, a solid component B and a polycarbosilane solution, wherein the solid component A is composed of Yb 2 O 3 Powder 50wt%, TiO 2 Powder 25wt% and HfO 2 The powder is composed of 25wt%, the Yb 2 O 3 Powder, the TiO 2 Powder and the HfO 2 The particle size D50 of the powder is 0.5 μm, and the solid component B is ZrO 2 Powder, the ZrO 2 The particle size D50 of the powder is 0.5 μm. In the two precursor impregnation solutions with gradient concentrations, the polycarbosilane solution is a xylene solution of polycarbosilane, in which the mass fraction of polycarbosilane is 20%; one precursor impregnation solution contains a solid component A with a mass fraction of 40% and a solid component B with a mass fraction of 20%, and the other precursor impregnation solution contains a solid component A with a mass fraction of 20% and a solid component B with a mass fraction of 40%.

[0134] In step ④, the density of the ceramic matrix composite material rich in solid component A and solid component B on the surface layer is 2.06 g / cm3 .

[0135] In this comparative example, after the subsequent step ⑤ of silicon dioxide infiltration process, the density of the ceramic matrix composite material prepared is 2.41 g / cm 3 .

[0136] Performance test: The ceramic matrix composite material prepared in this comparative example is tested at 1500℃, 90H 2 O-10O 2 The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 0.39mg / cm 2 The thermal conductivity of the prepared ceramic-based composite material is 5.9 W / (m·K) at 1500°C.

[0137] Comparative Example 8

[0138] Comparative Example 8 is substantially the same as Example 1, except that:

[0139] ③Prepare precursor impregnation solutions with gradient concentrations: prepare two precursor impregnation solutions with gradient concentrations, each of which is composed of a solid component A, a solid component B and a polycarbosilane solution, wherein the solid component A is composed of Yb 2 O 3 Powder 50wt%, TiO 2 Powder 25wt% and HfO 2 The powder is composed of 25wt%, the Yb 2 O 3 Powder, the TiO 2 Powder and the HfO 2 The particle size D50 of the powder is 0.5μm, the solid component B is MgO powder, and the particle size D50 of the MgO powder is 0.5μm. In the two precursor impregnation solutions with gradient concentrations, the polycarbosilane solution is a xylene solution of polycarbosilane, wherein the mass fraction of polycarbosilane is 20%; one precursor impregnation solution contains 40% solid component A by mass and 20% solid component B by mass, and the other precursor impregnation solution contains 20% solid component A by mass and 40% solid component B by mass.

[0140] In step ④, the density of the ceramic matrix composite material rich in solid component A and solid component B on the surface layer is 1.92 g / cm 3 .

[0141] In this comparative example, after the subsequent step ⑤ of silicon dioxide infiltration process, the density of the ceramic matrix composite material prepared is 2.30 g / cm 3 .

[0142] Performance test: The ceramic matrix composite material prepared in this embodiment is tested at 1500℃, 90H 2 O-10O 2 The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 0.37mg / cm 2 The thermal conductivity of the prepared ceramic-based composite material is 5.2 W / (m·K) at 1500°C.

[0143] Comparative Example 9

[0144] Comparative Example 9 is substantially the same as Example 1, except that:

[0145] ③Prepare precursor impregnation solutions with gradient concentrations: prepare two precursor impregnation solutions with gradient concentrations, each of which is composed of a solid component A, a solid component B and a polycarbosilane solution, wherein the solid component A is composed of Yb 2 O 3 Powder 50wt%, TiO 2 Powder 25wt% and HfO 2 The powder is composed of 25wt%, the Yb 2 O 3 Powder, the TiO 2 Powder and the HfO 2 The particle size D50 of the powder is 0.5 μm, and the solid component B is Gd 1.8 Yb 0.2 Zr 2 O 7 Powder, the Gd 1.8 Yb 0.2 Zr 2 O 7 The particle size D50 of the powder is 0.5 μm. In the two precursor impregnation solutions with gradient concentrations, the polycarbosilane solution is a xylene solution of polycarbosilane, in which the mass fraction of polycarbosilane is 20%; one precursor impregnation solution contains a solid component A with a mass fraction of 40% and a solid component B with a mass fraction of 20%, and the other precursor impregnation solution contains a solid component A with a mass fraction of 20% and a solid component B with a mass fraction of 40%.

[0146] In step ④, the density of the ceramic matrix composite material rich in solid component A and solid component B on the surface layer is 2.11 g / cm 3 .

[0147] In this comparative example, after the subsequent step ⑤ of silicon dioxide infiltration process, the density of the ceramic matrix composite material prepared is 2.53 g / cm 3 .

[0148] Performance test: The ceramic matrix composite material prepared in this comparative example is tested at 1500℃, 90H 2 O-10O 2 The weight loss rate of (vol.%) under water-oxygen corrosion conditions for 100h is 0.36mg / cm 2 The thermal conductivity of the prepared ceramic matrix composite material at 1500℃ is 6.8W / (m·K).

[0149] The performance indicators of the ceramic-based composite materials obtained in Examples 1 to 7 and Comparative Examples 1 to 9 are shown in Table 1. Compared with the comparative examples, the embodiments of the present invention show superiority in thermal conductivity and water-oxygen corrosion resistance. This is mainly due to the innovative method of preparing silicate by gradient concentration precursor impregnation liquid and silicon dioxide melt infiltration reaction adopted in the embodiments. This method enables the composite material to have excellent water-oxygen corrosion resistance while maintaining low thermal conductivity.

[0150] The embodiment of the present invention adopts a gradient concentration design to achieve the anti-water corrosion component (Yb 2 SiO 5 、TiSiO 4 、HfSiO 4 ) and high thermal insulation components (ZrSiO 4 Mg 2 SiO 4 ) is distributed in a gradient on the surface of the composite material. Benefiting from the synergistic effect of the anti-water vapor corrosion and high thermal insulation components, both the anti-water vapor corrosion ability of the surface layer and the thermal insulation ability of the surface layer are improved, thereby extending the service life of the material. Compared with the ceramic-based composite materials prepared using fixed concentration components or containing only one component in the comparative example, the ceramic-based composite materials prepared in the embodiments of the present invention are superior to the comparative examples in terms of thermal conductivity and weight loss rate. In particular, in terms of weight loss rate under high-temperature water-oxygen corrosion conditions, the embodiments show lower results, indicating that its anti-water-oxygen corrosion performance is superior. The ceramic-based composite materials prepared in the embodiments of the present invention have lower thermal conductivity at a high temperature of 1500°C and have better thermal insulation performance.

[0151] Table 1 Performance indicators of ceramic matrix composite materials obtained in Examples 1 to 7 and Comparative Examples 1 to 9

[0152]

[0153] The parts of the present invention that are not described in detail are well-known technologies for those skilled in the art. Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention is described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a ceramic-based composite material having both water-oxygen corrosion resistance and high thermal insulation performance, characterized in that: The method comprises the following steps: (1) Preparation of porous ceramic-based composite materials; (2) using a polycarbosilane solution as an impregnation solution, and densifying the porous ceramic-based composite material through a precursor impregnation and cracking process to obtain a preliminarily densified ceramic-based composite material; (3) preparing n precursor impregnation solutions with gradient concentrations, each precursor impregnation solution comprising a solid component A, a solid component B and a polycarbosilane solution, wherein the solid component A comprises ytterbium oxide powder, titanium oxide powder and hafnium oxide powder, and the solid component B comprises zirconium oxide powder and magnesium oxide powder; (4) densifying the preliminarily densified ceramic matrix composite material by a precursor impregnation cracking process in sequence with n gradient concentrations of the precursor impregnation liquid to obtain a ceramic matrix composite material having a surface layer containing a solid component A and a solid component B; wherein the content of the solid component A in the surface layer shows a decreasing trend, and the content of the solid component B in the surface layer shows an increasing trend; (5) The ceramic-based composite material having a surface layer containing solid component A and solid component B is placed in a silicon dioxide powder for infiltration reaction to obtain a ceramic-based composite material having both water and oxygen corrosion resistance and high thermal insulation performance.

2. The preparation method according to claim 1, characterized in that: In the precursor impregnation solutions with n gradient concentrations, the content of the solid component A shows a decreasing trend, and the content of the solid component B shows an increasing trend; n≥2 and n is a positive integer; The concentration range of the solid component A in the n gradient concentration precursor impregnation solutions is 10-50wt%, and the concentration range of the solid component B in the n gradient concentration precursor impregnation solutions is 10-50wt%; and / or The surface layer of the ceramic-based composite material with both water-oxygen corrosion resistance and high thermal insulation performance is a mixed dense layer containing ytterbium silicate, titanium silicate, hafnium silicate, zirconium silicate, magnesium silicate, silicon carbide, silicon dioxide and a fiber skeleton, wherein the total content of ytterbium silicate, titanium silicate and hafnium silicate in the surface layer shows a decreasing trend, and the total content of zirconium silicate and magnesium silicate in the surface layer shows an increasing trend.

3. The preparation method according to claim 1 or 2, characterized in that: In step (1): The porous ceramic-based composite material is obtained by depositing an interface layer on the fibers of a fiber braid; Preferably, the fiber braid is a carbon fiber braid or a silicon carbide fiber braid; Preferably, the density of the fiber braid is 0.4-0.7 g / cm 3 ; Preferably, the interface layer is one or more of a pyrolytic carbon interface layer, a silicon carbide interface layer or a boron nitride interface layer; Preferably, the density of the porous ceramic-based composite material is 0.8 to 1.2 g / cm 3 .

4. The preparation method according to claim 1 or 2, characterized in that: In step (2): The polycarbosilane solution is a xylene solution of polycarbosilane, and preferably, the mass fraction of polycarbosilane in the polycarbosilane solution is 35-60%; and / or Repeat the precursor impregnation and cracking process several times until the density is 1.3-1.5 g / cm 3 Preliminary densification of ceramic matrix composites.

5. The preparation method according to claim 1 or 2, characterized in that: In step (3): The polycarbosilane solution is a xylene solution of polycarbosilane, and preferably, the mass fraction of polycarbosilane in the polycarbosilane solution is 10 to 30%; The particle size D50 of the ytterbium oxide powder, titanium oxide powder and / or hafnium oxide powder is 0.1 μm to 1 μm; and / or The solid component A comprises, by mass fraction, 40-60% of ytterbium oxide powder, 20-30% of titanium oxide powder and 20-30% of hafnium oxide powder.

6. The preparation method according to claim 1 or 2, characterized in that: In step (3): The particle size D50 of the zirconium oxide powder and / or the magnesium oxide powder is 0.1 μm to 1 μm; The solid component B contains 40-60% of zirconium oxide powder and 40-60% of magnesium oxide powder by mass fraction.

7. The preparation method according to claim 1 or 2, characterized in that: In step (4): The thickness of the ceramic-based composite material containing solid component A and solid component B on the surface layer is 500 to 2000 μm; and / or The density of the ceramic-based composite material containing solid component A and solid component B on the surface layer is 1.8-2.1 g / cm 3 .

8. The preparation method according to claim 1 or 2, characterized in that: In step (5): The particle size D50 of the silicon dioxide powder is 0.1 μm to 1 μm; The temperature of the infiltration reaction is 1400-1700° C., and the time of the infiltration reaction is 60-180 min; and / or The heating rate to the temperature of the infiltration reaction is 2 to 4°C / min.

9. The preparation method according to claim 1 or 2, characterized in that: In step (5): The thickness of the mixed dense layer is 500 to 2000 μm; The density of the ceramic-based composite material having both water-oxygen corrosion resistance and high thermal insulation performance is 2.2-2.5 g / cm 3 ; The ceramic-based composite material having both water-oxygen corrosion resistance and high heat-insulating performance has a thermal conductivity of no more than 5 W / m·K at 1500° C. and has excellent water-oxygen corrosion resistance at 1200-1500° C.

10. A ceramic-based composite material having both water-oxygen corrosion resistance and high thermal insulation properties, obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Thermal-environmental barrier coating and preparation method and application thereof

    CN113278909A

  • Multiphase oxide ceramic modified ceramic-based composite material and preparation method thereof

    CN117923928A

  • Composite member

    CN103394668A

  • Gradient C / ZrC-SiC ultrahigh-temperature ceramic-based composite material and preparation method thereof

    CN112341229A

  • Low-cost carbon fiber reinforced metal-ceramic matrix composite material for aerospace thermal protection system and preparation method of low-cost carbon fiber reinforced metal-ceramic matrix composite material

    CN116219329A